VD_FINDINFO Décision / 2012 / 64 vom 13. Dezember 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, SOUPÇON, RISQUE DE COLLUSION, RISQUE DE FUITE, PROLONGATION | 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)